Consumption and everyday life - Paterson, Mark 1972- (Routledge, Taylor & Francis Group, 2023)
"With an emphasis on everyday life, this respected text offers a lively and perceptive account of the key theories and ideas which dominate the field of consumption and consumer culture. This third revised and expanded edition is a major update of the text of the second edition, adding new chapters on youth culture and consumption, retail psychology, gender and consumption, the globalization of food and FairTrade, and digital consumption and platform capitalism. Various theoretical perspectives - such as theories of practice, semiotics, to psychoanalysis - are used to illustrate concepts and trends in consumption, whilst a wide range of engaging and up-to-date case studies are employed throughout to provide historical context and illustrate forms of consumption. Written by an experienced teacher, the book offers an accessible and thought-provoking introduction to the concept of consumption for students in sociology, cultural studies, history, anthropology, and social psychology"--